Veno-Arterial Partial Pressure of Carbon Dioxide Difference as a Metric of Systemic Oxygen Delivery: Insights from a Correlative Meta-Analysis - Loomba, Rohit S.; Farias, Juan S.; Savorgnan, Fabio; Acosta, Sebastian; Flores, Saul; Villarreal, Enrique G. (Journal of Pediatric Intensive Care, 2022)
The assessment of cardiac output and adequacy of systemic oxygen delivery in children after cardiac surgery require the use of an aggregate of hemodynamic monitors and blood tests. There are previously published data regarding the utility of the veno-arterial partial pressure of carbon dioxide difference (AVDco2) to help with this. This study pooled data on the correlation of AVDco2 with other metrics of cardiac output and systemic oxygen delivery such as arteriovenous oxygen saturation difference, venous saturation, and serum lactate. A systematic review of the literature was done to identify studies analyzing the correlation of AVDco2 with other hemodynamic and laboratory values. Data were extracted, and correlation coefficients were pooled for each specific comparison to create a point estimate for the overall correlation. A total of four studies with 350 patients and 809 paired blood gases were pooled. Adequate data were available to assess the correlation of AVDco2 with arteriovenous oxygen saturation difference, venous saturation, and serum lactate. There was a significant, moderate correlation with arteriovenous oxygen saturation difference and venous saturation. A significant, weak correlation with serum lactate was found. The AVDco2 has significant, moderate correlations with other metrics of the adequacy of systemic oxygen delivery such as arteriovenous oxygen saturation difference and venous saturation. There was a significant but only weak correlation with serum lactate. AVDco2 may be complementary to assess the adequacy of cardiac output and systemic oxygen delivery.
Keywords: carbon dioxide; cardiac output; oxygen consumption; serum lactate; pediatric patients; cardiac surgery